2018
DOI: 10.1002/cncr.31342
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in the survivorship experience among Latina survivors of breast cancer

Abstract: Latina survivors of BC experienced disparities in BC knowledge and satisfaction with information received, but believed themselves to be prepared for survivorship and were as satisfied with providers, care received, and discussions with physicians as non-Latinas. Cancer 2018;124:2373-80. © 2018 American Cancer Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 57 publications
1
17
0
Order By: Relevance
“…Compared to white breast cancer survivors and more acculturated Latinas, less acculturated Latina breast cancer survivors report less involvement in treatment decision making, greater treatment decision making regret, less satisfaction with breast cancer care information provided, a more limited understanding of their diagnosis and treatment, lower self-efficacy for interacting with physicians, and worse patient-physician relationships [11][12][13][14][15][16]. Among Latina breast cancer survivors, greater English proficiency was associated with better communication effectiveness specific to treatment decision making, and better communication predicted greater satisfaction, which, in turn, predicted better quality of life [17].…”
Section: Introductionmentioning
confidence: 94%
“…Compared to white breast cancer survivors and more acculturated Latinas, less acculturated Latina breast cancer survivors report less involvement in treatment decision making, greater treatment decision making regret, less satisfaction with breast cancer care information provided, a more limited understanding of their diagnosis and treatment, lower self-efficacy for interacting with physicians, and worse patient-physician relationships [11][12][13][14][15][16]. Among Latina breast cancer survivors, greater English proficiency was associated with better communication effectiveness specific to treatment decision making, and better communication predicted greater satisfaction, which, in turn, predicted better quality of life [17].…”
Section: Introductionmentioning
confidence: 94%
“…The literature review on breast cancer survivorship and its determinants indicated significant unmet survivorship care needs among Latina breast cancer survivors including issues related to finance, symptom management, and survivorship care related information [4,25] and poor mental and physical health and low quality of life [26][27][28]. The determinants for the optimal use of SCP included knowledge about survivorship related issues [4,29,30], psychological distress (i.e., anxiety and fear concerning cancer recurrence) [26,27,31], and lack of confidence in patient-physician communication and management of chronic illness [30,32,33].…”
Section: Step One: Needs Assessmentmentioning
confidence: 99%
“…These challenges are of special importance among Latinas who, compared to non-Hispanic Whites, are more likely to be diagnosed at an advanced cancer stage [3]. Latina breast cancer survivors have lower survivorship knowledge and greater dissatisfaction with care information [4], unmet physical symptom management, lack of social support, and need for formal transition to follow-up care compared to non-Latina counterparts [5].…”
Section: Introductionmentioning
confidence: 99%
“…Among Latinas/Hispanics (henceforth referred to as Latinas), breast cancer is the most commonly diagnosed cancer and the leading cause of cancer-related deaths [1]. Compared with non-Latina breast cancer survivors (BCSs), Latina BCSs report multiple disparities including poorer health-related quality of life (HRQoL), greater symptom burden, greater cancer-related psychosocial needs [2-4], less breast cancer knowledge, and more dissatisfaction with information related to breast cancer care [5]. Prior studies show that poorer HRQoL is related to lower levels of adherence to disease surveillance and adjuvant treatment [6,7], and interventions designed to improve HRQoL specifically for Latina BCSs can improve adherence to posttreatment care and health outcomes [2,8,9].…”
Section: Introductionmentioning
confidence: 99%